Kajian Kompensasi MCK dengan Septiktank Biofilter sebagai Upaya Penurunan Beban Pencemar BOD pada Sungai Bedadung - Dheas Rizqi Ameilia; Firra Rosariawari; Aprilia Permata Sari (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Compensation is an effort to reduce the pollution load from other sectors to replace the wastewater load that will be discharged by businesses and/or activities due to river water quality being exceeded. Currently, most large rivers in Indonesia have exceeded the water quality standards set by the government. The one of the hospitals in Jember plans to discharge wastewater into the Bedadung River. However, the Biochemical Oxygen Demand (BOD) quality standard for the Bedadung River has been exceeded. Therefore, alternative compensation activities are needed to reduce the BOD levels of the Bedadung River. Bathing, Washing, and Toilet (MCK) facilities with biofilter septic tanks were chosen. This technology is considered to be able to effectively reduce the BOD concentration of domestic waste before being discharged into the environment. This study aims to calculate the potential for reducing the BOD pollutant load in Bedadung River water if compensation is carried out through the construction of MCK with a biofilter septic tank system, so that it is expected to provide a significant contribution to improving river water quality while supporting the sustainability of hospital activities.